PENGARUH INVESTASI SWASTA (PMDN), BELANJA DAERAH DAN PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI LAMPUNG - Siti Munawaroh (Business and Enterpreneurship Journal (BEJ), 2023)
This study aims to analyze the effect of investment, regional spending and local revenue directly on economic growth in Lampung province. This study uses secondary data in the form of time series data, namely from 2012-2021 which was obtained through the Central Statistics Agency (BPS). This study uses an empirical approach, namely research on social and natural phenomena. The type of research chosen is quantitative research, namely research that emphasizes testing theories through measuring research variables with numbers and the data is processed, and conducting data analysis with statistical procedures to analyze the relationship between variables and hypotheses. The results of the study show that the independent variables affect Economic Growth (PE) in Lampung Province. Meanwhile, partially, the variables Investment (INV), Regional Expenditures (BD) and Regional Original Income (PAD) have an effect on Economic Growth (PE) in Central Lampung Regency. For this reason, the government should not only pursue high economic growth rates, but more than that, economic growth must be of good quality and equity, namely growth that can be felt by all levels of society  Keywords: investment,regional spending, regional income and economic growth